Get set for psychology - Wright, Peter, M.A., D.Phil; Macleod, Hamish (Edinburgh : Edinburgh University Press, 2006)
We are all psychologists. As human beings, we all have intuitive beliefs and ideas about why people do the things they do, and the ability to form such beliefs is an important part of surviving and getting on in the world. Indeed those few individuals who lack this ability are severely disadvantaged. Studying psychology at a university level is both like and quite unlike these natural skills. Many of our beliefs about the social world are accurate, but some are unfortunately quite incorrect and misleading. How do we know when we are correct? How do we go about finding out? Our natural inclination is to seek evidence to confirm our beliefs, and therein lies prejudice. The answer from psychology is to form hypotheses and systematically test them against the evidence, and this is what makes psychology a science. This book aims to encourage and enable the reader to link a natural interest in human (and animal) behaviour with the sorts of models and theories that are used by academic psychologists. Part 1 covers the main areas of psychological endeavour, seeking to provide engaging examples of psychological questions, rather than to provide an exhaustive account. Part 2 addresses the business of living and studying at university, inviting the reader to reflect on what psychology has to say about being a student.
Part I. Understanding Psychology. 1. How to use this book -- 2. Statistical thinking -- 3. Practical classes -- 4. Biological bases of behaviour -- 5. Perception -- 6. Cognitive psychology -- 7. Developmental psychology -- 8. Social psychology -- 9. Individual differences -- Part II. The University Experience and Psychology. 10. Getting the most out of lectures -- 11. Learning in small groups -- 12. Writing to be read -- 13. Online learning -- 14. Preparing for and sitting examinations.
Includes bibliographical references and index.
Print version record.
English.
Electronic reproduction.
Mode of access: World Wide Web.
JSTOR
Keywords: Psychology -- Study and teaching (Higher); PSYCHOLOGY -- Education & Training; PSYCHOLOGY -- General; Psychology -- Study and teaching (Higher)